The Japanese economic system and its historical origins - Herbert, Susan; Okazaki, Tetsuji; Okuno - Fujiwara, Masahiro (Oxford University Press, 1999)
This book examines the structure and evolution of Japan's economic system, tracing its historical roots from the prewar period to the postwar era. It analyzes how institutional arrangements, government policies, and business practices shaped Japan's industrial organization and economic performance. Through historical and comparative perspectives, the authors explore the interplay between state and market forces that led to Japan's distinctive model of capitalism.